2008
DOI: 10.4161/cbt.7.3.5423
|View full text |Cite
|
Sign up to set email alerts
|

Tumor chemo-immunotherapy using gemcitabine and a synthetic dsRNA

Abstract: Both gemcitabine and synthetic double-stranded RNA (dsRNA) are known to be proapoptotic and immuno-stimulatory (-modulatory). We sought to evaluate the extent to which a combination therapy using gemcitabine and a synthetic dsRNA, polyinosine-cytosine (poly(I:C)), would improve the resultant anti-tumor activity. Using model lung and breast cancers in mice, we demonstrated that combination treatment of tumor-bearing mice with the poly(I:C) and gemcitabine synergistically delayed the tumor growth and prolonged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Several studies have demonstrated that the activation of TLR3 by dsRNA directly inhibits cell proliferation and induces apoptosis in tumor cells (9)(10)(11)29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the activation of TLR3 by dsRNA directly inhibits cell proliferation and induces apoptosis in tumor cells (9)(10)(11)29).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of dsRNA to directly stimulate TLR3 and produce type I interferons (IFNs) was primarily the rationale for its clinical use in cancer patients (8). More recently, several studies have demonstrated that the activation of TLR3 by dsRNA directly inhibits cell proliferation and induces apoptosis in tumor cells (9)(10)(11). In view of these promising effects, the use of dsRNA-derived compounds in combination with anticancer agents for chemoimmunotherapy warrants robust investigation (12).…”
Section: Introductionmentioning
confidence: 99%
“…The TLR3 gene codes for an endoplasmic receptor of the pattern-recognition receptors (PRRs) family that recognizes double-stranded RNA (dsRNA) and plays an important role in the innate immune response triggered by viral infection. Several studies demonstrated that activation of TLR3 by dsRNA directly inhibited cell proliferation and induced apoptosis in tumor cells [116118]. Synthetic dsRNAs (e.g., polyinosine-cytosine, poly I:C; polyadenylic-polyuridylic, poly A:U) were demonstrated to be one of the agents in tumor chemotherapy demonstrating favorable outcome in clinical trials [119].…”
Section: Innate Antibacterial Signalingmentioning
confidence: 99%
“…Finally, G administration like D induces a fast release of TNFα and other inflammatory Th1 cytokines. [14][15][16]31 We have hypothesized that antigen release consequent to DG chemotherapy, when integrated with GM-CSF + IL-2 immunoadjuvant treatment, may lead to the generation of a more active CTLs response, able to contribute to the achievement of a more effective antitumor response. A similar model has already been investigated in advanced colorectal carcinoma patients, where a G-containing polychemotherapy regimen (GOLF) integrated with GM-CSF + IL-2 immunoadjuvant treatment led to an impressive antitumor activity in patients who had received at least two/three lines of chemotherapy [58% objective response rate; 91% control disease rate, prolonged TTP (13 months) and OS (20 months)].…”
Section: Methodsmentioning
confidence: 99%
“…It has been in fact reported that G acts as a powerful immune-adjuvant agent for anticancer vaccine and immunotherapeutic strategies with a mechanism probably related to its selective ability to kill immunosuppressive T regulatory cells and promote a Th1 cytotoxic response. [14][15][16] Moreover, D has been described as stimulating/activating agent of either monocyte and lymphocyte proliferation through the lypopolysaccaride cytoskeletal pathway. 17,18 Furthermore, immunological studies in cancer patients during D administration have shown a significant increase of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%